Role of cholesterol in the development and progression of breast cancer - Llaverias, Gemma; Danilo, Christiane; Mercier, Isabelle; Daumer, Kristin; Capozza, Franco; Williams, Terence M; Sotgia, Federica; Lisanti, Michael P; Frank, Philippe G (The American journal of pathology, 2011)
Diet and obesity are important risk factors for cancer development. Many studies have suggested an important role for several dietary nutrients in the progression and development of breast cancer. However, few studies have specifically addressed the role of components of a Western diet as important factors involved in breast cancer initiation and progression. The present study examined the role of cholesterol in the regulation of tumor progression in a mouse model of mammary tumor formation. The results suggest that cholesterol accelerates and enhances tumor formation. In addition, tumors were more aggressive, and tumor angiogenesis was enhanced. Metabolism of cholesterol was also examined in this mouse model. It was observed that plasma cholesterol levels were reduced during tumor development but not prior to its initiation. These data provide new evidence for an increased utilization of cholesterol by tumors and for its role in tumor formation. Taken together, these results imply that an increase in plasma cholesterol levels accelerates the development of tumors and exacerbates their aggressiveness.